A realidade socioambiental de Laranjal do Jari/AP: soluções apontadas por moradores na perspectiva da educação popular - Paixão, Eliana do Socorro de Brito (2013)
The city Laranjal do Jari, in the state of Amapá, Brazil, has been historically affected by capitalist enterprises, for example, with Jari Project, implemented in the area in 1967. Laranjal do Jari is the third biggest city in the state and it concentrates 94.9% of the population of the city, totalizing 39.942 inhabitants. Its total area is of only 12.355mi² (32 km²) out of the 12.035mi² (31.170,30 km²) incorporated by the city. The remaining lands were destined to parks, reservations and private areas. The city emerged as an urban center called Beiradão (which means in the dialect of the state of Amazonia an agglomeration constituted at the shores of a river) due to the disorderly occupation at the shores of Jari River, where a big portion of the citizens still live in stilt houses, located in fragile areas (várzea forests), creating a gigantic river slum prone to problems such as fires and floods. The poor living conditions plus hazardous environment observed in the open sewage, high amount of solids in the water, storage of human waste under the houses and lack of a sewage system among other ills, point the poverty, circles at around 46.20%.This situation is, quite often, also present in land areas of the city. The conditions presented here instigated me to do some survey in order to allow me to clarify the following issue: Which were the solutions pointed out by a group of citizens of Laranjal do Jari to solve these problems considering their popular assumptions to solve social and environmental issues, having in mind the purpose of allowing subsidies from future governmental actions? The main goal of the research was to identify and analyze solutions to the social and environmental issues in Laranjal do Jari, wherein these solutions pointed out by a group of local citizens in light of the assumptions of the popular education and allowing future governmental actions in terms of subsidizing. The research was based in the historical and dialectical methods and focused in the qualitative approach. The activities held in the field were conceived at the Círculo de Cultura and the processing of data was inspired in content analysis. The individuals that participated in the research were citizens of Laranjal do Jari, specifically from the following neighborhoods: Sagrado Coração de Jesus, Malvinas, Agreste and Mirilândia. Among the results, the research showed that the social and environmental issues in Laranjal do Jari were inheritances from the implementation of Jari Project and its consolidation represents a direct relation to the permanence of the project in the area. It became evident in the statements and group debates a general disbelief in the actions of the government, considered to be incapable to respond positively to the worries of the population. When it comes to propose changes in the built environment, it is vital to hear from those who know the situation that they live in, and such knowledge was clearly expressed by the local citizens through their statements and highly critical positions towards the current reality, so much so that the citizens went on to search in poetry the freedom of speech to face the reality seen by them.